Hubungan Efikasi Diri terhadap Tingkat Kepatuhan Minum Obat pada Pasien Tuberkulosis Paru : Correlation between Self-Efficacy and Compliance with Taking Medication in Pulmonary Tuberculosis Patients - Yonatan Bage Girsang (MPI Press, 2023)
Introduction: Non-adherence to pulmonary tuberculosis treatment is one of the causes of pulmonary tuberculosis cases which is still high, the number of pulmonary TB cases in Indonesia was 420.994 cases in 2017. Patient confidence in treatment is a determining factor for health behavior and the extent of patient compliance with treatment. Objectives: This study aims to identify the relationship between self-efficacy and adherence to medication in pulmonary tuberculosis patients at Pasir Putih Public Health Center, Depok City in 2021. Method: This research uses a quantitative approach with a cross-sectional study design. There are 30 respondents at the Pasir Putih Public Health Center. Data were collected using direct interviews. The questionnaires used were self-efficacy questionnaires to assess self-efficacy and Morinsky Medication Adherence Scales to assess respondents' medication adherence. Result: The results of the research p-value between the relationship of self-efficacy to the level of adherence to taking medication in patients with pulmonary tuberculosis 0.004 < 0.005, with the analysis of respondents having poor self-efficacy as much as 53.3% had obedient behavior in taking medication. And based on the results of the study, the OR value (1,417) means that it can be seen that the patients with good self-efficacy have a 1.4 times chance of experiencing a good level of compliance compared to those who have poor efficacy with a sufficient level of compliance. Conclusion: There is a significant relationship between self-efficacy and medication adherence in pulmonary tuberculosis patients at the Pasir Putih Public Health Center, Depok City in 2021 (P=0.004), and efforts are needed to improve self-efficacy and medicate adherence in Pulmonary Tuberculosis Patients at Pasir Putih Health Center, Depok City.